Estimating ages of white‐tailed deer: Age and sex patterns of error using tooth wear‐and‐replacement and consistency of cementum annuli. (28th October 2014) - Storm, Daniel J.; Samuel, Michael D.; Rolley, Robert E.; Beissel, Thomas; Richards, Bryan J.; Van Deelen, Timothy R.
ABSTRACT The age structure of harvested animals provides the basis for many demographic analyses. Ages of harvested white‐tailed deer (Odocoileus virginianus) and other ungulates often are estimated by evaluating replacement and wear patterns of teeth, which is subjective and error‐prone. Few previous studies however, examined age‐ and sex‐specific error rates. Counting cementum annuli of incisors is an alternative, more accurate method of estimating age, but factors that influence consistency of cementum annuli counts are poorly known. We estimated age of 1, 261 adult (≥1.5 yr old) white‐tailed deer harvested in Wisconsin and Illinois (USA; 2005–2008) using both wear‐and‐replacement and cementum annuli. We compared cementum annuli with wear‐and‐replacement estimates to assess misclassification rates by sex and age. Wear‐and‐replacement for estimating ages of white‐tailed deer resulted in substantial misclassification compared with cementum annuli. Age classes of females were consistently underestimated, while those of males were underestimated for younger age classes but overestimated for older age classes. Misclassification resulted in an impression of a younger age‐structure than actually was the case. Additionally, we obtained paired age‐estimates from cementum annuli for 295 deer. Consistency of paired cementum annuli age‐estimates decreased with age, was lower in females than males, and decreased as age estimates became less certain. Our results indicated that errors in the wear‐and‐replacement techniques are substantial and could impact demographic analyses that use age‐structure information. © 2014 The Wildlife Society.